2011
DOI: 10.1177/1054773811419842
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Excessive Daytime Sleepiness and Fatigue in Adults With Heart Failure

Abstract: Little is known about excessive daytime sleepiness (EDS) in heart failure (HF). The aim of this cross-sectional descriptive study was to describe the prevalence of EDS and factors associated with it in HF. A secondary purpose was to explore the correlates of fatigue. We enrolled a consecutive sample of 280 adults with a confirmed diagnosis of chronic HF from three outpatient settings in the northeastern US. Patients with major depressive illness were excluded. Clinical, sociodemographic, behavioral, and percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 67 publications
(95 reference statements)
4
28
1
4
Order By: Relevance
“…The current study's DS prevalence, as assessed with the ESS, was 50.8% using a cut‐off of ≥6 and 21.3% with a cut‐off of ≥10. This prevalence is higher than in the general population, which ranges from 1.4% to 8% , yet lower than those reported (ESS cut‐off ≥10) in other chronically ill populations, for example, hemodialysis (27%) , heart failure (23.6%) , gastro‐esophageal reflux disease (48.8%) , and primary biliary cirrhosis (51%) . Our multivariate model showed that higher DS scores were associated with more immunosuppressive NA.…”
Section: Discussioncontrasting
confidence: 59%
“…The current study's DS prevalence, as assessed with the ESS, was 50.8% using a cut‐off of ≥6 and 21.3% with a cut‐off of ≥10. This prevalence is higher than in the general population, which ranges from 1.4% to 8% , yet lower than those reported (ESS cut‐off ≥10) in other chronically ill populations, for example, hemodialysis (27%) , heart failure (23.6%) , gastro‐esophageal reflux disease (48.8%) , and primary biliary cirrhosis (51%) . Our multivariate model showed that higher DS scores were associated with more immunosuppressive NA.…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, the more fatigue is perceived, the poorer the sleep quality experienced by participants, similar to the finding from the previous study by Nasiri et al (2016). Some studies also confirmed the associations of fatigue and global PSQI score using different kind of fatigue measurements (Dos Santos et al, 2011, Fink et al, 2012, Riegel, 2012.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that the higher the daytime dysfunction, the more severity, distress, interference in ADL, and longer fatigue participants had. Riegel (2012) found that patients with HF with worse daytime dysfunction are more likely to have fatigue. The findings suggest that daytime dysfunction may result in altered daily activities and recreational life.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive daytime sleepiness, a consequence of sleep disturbance, was chosen as a variable in this study because of its prevalence in individuals with heart failure (Reddeker & Stein ) and association with worse functional status and lack of physical activity (Riegel et al . ). In the present study, Cronbach's alpha on this subscale was 0·74.…”
Section: The Studymentioning
confidence: 97%